Breaking barriers: advancing cellular therapies in autoimmune disease management - Fu, Yanhong; Feng, Chunjing; Qin, Shan; Xing, Zhiyao; Liu, Chong; Liu, Zichuan; Yu, Hongjian (Frontiers in Immunology, 2024)
Autoimmune diseases occur due to a dysregulation within the immune system, leading to an aberrant assault on the organism’s own tissues. The pathogenesis of these conditions is multifactorial, encompassing intricate interplays among genetic predispositions, environmental determinants, and hormonal fluctuations. The spectrum of autoimmune diseases is broad, impacting a multitude of organ systems, with notable examples such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), multiple sclerosis (MS), psoriasis, and vitiligo. Despite substantial progress in therapeutic interventions over recent years, a definitive cure for autoimmune diseases has yet to be realized, with existing modalities largely providing palliative care. Cellular therapy is considered the fourth pillar in the management of oncological disorders subsequent to surgical resection, radiotherapy, and chemotherapy. Cellular therapies have shown potential in augmenting immune competence and eliminating of targeted neoplastic cells in a spectrum of cancers. As targeting specific molecules on the surface of autoreactive B and T cells, such as CD19, BCMA, CD20, and CTLA-4, cellular therapies are emerging as promising approaches for the treatment of autoimmune diseases. This review delineates the advancements in the application of cellular therapies applied recently for autoimmune diseases and proposes considerations for the advancement of novel therapeutic strategies.